Snow engineering V : proceedings of the fifth International Conference on Snow Engineering, 5-8 July 2004, Davos, Switzerland /: proceedings of the fifth International Conference on Snow Engineering, 5-8 July 2004, Davos, Switzerland. (2004) - Unknown
No abstract available